Pelayanan Publik Pada Masa Pandemi Covid-19 di Kecamatan Sambaliung Kabupaten Berau - Denny Nazaria Rifani (Sawala : Jurnal Administrasi Negara, 2021)
This study was conducted to identify and describe the implementation of public services during the Covid-19 pandemic in Kecamatan Sambaliung, Kabupaten Berau. The dimensions of measurement in this research are the improvement of services during the Pandemic by the Ombudsman RI including Clear information on service standards, online service systems, an adaptation of facilities/infrastructure/service facilities, and competence of service implementers. The type of research used in this research is descriptive qualitative with primary data and secondary data. Data analysis was carried out through data reduction, data presentation, conclusion drawing, and verification. The results of this study indicate that the implementation of public services during the Covid-19 Pandemic can still be carried out but in a different way than usual, the standard of service provided is following the circular letter of the Kabupaten Berau Government which refers to the rules of the Central Government, facilities/infrastructure/facilities have been provided following the recommendations of the Ministry of Health, good competence of officers and have a lot of experience placed in their respective fields to provide fast and appropriate services. Must improve the implementation of information technology-based services, because there is still no online-based service.